The Development Integrated Agricultural Ecotourism Based on WEBGIS to Support Community Welfare in Kutaliman Village - Hanifa, Hana; Syarifah, Risqa Naila Khusna; Novitasari, Dian; Marjuki (Prospect Publishing, 2024)
The poverty conditions occurring in the midst of society are caused by various interconnected factors that worsen the situation. Kutaliman Village is one of the villages in Banyumas Regency with a relatively high unemployment rate (55%). This is regrettable considering the abundant natural resources in Kutaliman Village, such as fertile land, cool temperatures, abundant water, and the beauty of the natural landscape. Efforts to address these issues involve utilizing integrated farming as a tourist attraction that can enhance recreational experiences with direct education in the open environment. The role of the Self-Reliant Agriculture and Rural Training Centre (P4S) Sida Mukti is crucial in developing these potentials by engaging the local community and youth. This service activity is implemented by expanding the Agroecotourism Area, involving livestock farms, fish ponds, and the farmland owned by residents as integrated farming education destinations during a visit. Additionally, the creation of a WEBGIS-based map is necessary to facilitate visitors in accessing the integrated farming destinations they plan to visit.